Improving Grade IV Students' Cognitive Learning Outcomes through Rotary Wheel Learning Media at SDN Socah 2 Bangkalan. - Sri Wahyuningsih Muasin; Lailatul Mukarromah; Sintia Febriyanti; Alif Ilham Wahyudi M.; Agung Setyawan (Journal of Action Research in Education, 2026)
This study aims to improve the cognitive learning outcomes in Mathematics regarding simple fractions among 21 fourth-grade students at Elementary School Socah 2 using the Pizza Spinning Wheel learning media. The research addresses students' difficulties in understanding, determining correct operations, and connecting fraction concepts to everyday situations to solve story problems. The Pizza Spinning Wheel was selected to concretize fraction concepts and enhance learning activity. This Classroom Action Research (CAR) was conducted in two cycles, each comprising planning, implementation, observation, and reflection. Data were collected via observations, interviews, tests, and documentation. A mixed quantitative and qualitative descriptive approach was employed for data analysis, including completeness percentage calculations and qualitative stages (data reduction, presentation, and conclusion). The results demonstrate that the Pizza Spinning Wheel effectively improved students' cognitive learning outcomes. Student learning completion increased from 67% in Cycle I to 81% in Cycle II. In conclusion, this media is highly effective for teaching simple fractions. Teachers are encouraged to adopt this alternative tool to enhance students' conceptual understanding and word problem-solving skills in Mathematics.